Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan PT. Sumber Bening Lestari - Alfiah Said; Widi Astutik (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
PT Sumber Bening Lestari is an attractive bottled mineral water company for various community needs, the company is located in Pandaan, East Java. This study aims to examine and provide empirical evidence about the analysis of the influence of leadership style and compensation on employee performance at PT Sumber Bening Lestari. The research instrument used was a questionnaire distributed to 70 employees of the production department taken using purposive sampling techniques. Furthermore, the collected data was analyzed using statistical analysis, namely descriptive statistical analysis and inferential statistical analysis. The results of this study indicate the results of the study found that leadership style variables influence employee performance, compensation variables affect employee performance and simultaneously leadership style variables and compensation affect the performance of employees of PT Sumber Bening Lestari Pandaan